Long-term therapy with intrathecal baclofen improves quality of life in children with severe spastic cerebral palsy. (May 2017) - Kraus, Tanja; Gegenleitner, Kathrin; Svehlik, Martin; Novak, Michael; Steinwender, Gerhardt; Singer, Georg
Abstract: Introduction: Children with severe spastic cerebral palsy (CP) are highly limited in daily life activities causing a reduced quality of life (QoL). This is partly due to an increased muscle tone causing pain and contractures. Continuous intrathecal infusion of baclofen (ITB) reduces the spasticity of affected patients. The hypothesis of the present study was that ITB leads to a significant improvement of QoL in non-ambulant children with CP. Patients and Methods: 13 patients (10 male, 3 female, mean age 14 years) were included. Mean time between pump implantation and follow-up was 60 months (range, 12–100). QoL was assessed before and after baclofen pump implantation using standardized questionnaires (CP CHILD, KINDL). Spasticity was evaluated using the modified Ashworth Scale (MAS) at the two time points. Results: QoL evaluated with the CPCHILD questionnaire and the KINDL improved from pre - implantation to follow-up. MAS markedly decreased from 3.8 to 1.7. All interviewed participants indicated that their expectations had been met and that they would choose ITB treatment again. Conclusion: Intrathecal treatment of baclofen is an excellent method for spasticity management in children with severe cerebral palsy. Quality of life sustainably improves, parents' satisfaction is high and the level of spasticity decreases. Therefore, baclofen treatment can be highly recommended in non-ambulant children with CP suffering from spasticity. Highlights: Intrathecal treatment of baclofen (ITB) was used in children with severe spastic cerebral palsy (CP). Quality of life significantly improved and spasticity decreased at a mean follow-up of 60 months. ITB is an excellent method for spasticity management in children with severe spastic cerebral palsy.